Faktor Penentu Keputusan Konsumen dalam Mengkonsumsi Teh Celup Sariwangi (Studi Kasus pada Konsumen Tiara Dewata Group di Kota Denpasar) - EVA YUNITA; I MADE SUDARMA; IDA AYU LISTIA DEWI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2017)
Determinants of Consumer Decisions in Consuming Sariwangi Dye Tea(Case Study on Tiara Dewata Consumer Group in Denpasar City) The consumers’ decision in purchasing Sariwangi tea bag products is affected byconsumer characteristics and marketing mix elements. These variables affect thebuying decision processes so as to produce a buying decision. This research wasconducted at supermarkets in Denpasar City with the aim to identify the factors thatplay a role in consumer decision to buy Sariwangi tea bags and analyze decisionprocesses of purchasing Sariwangi tea bags by consumers in Denpasar City. In thisresearch, the method used was descriptive-quantitative analysis method andqualitative-descriptive analysis. The results showed that all variables had a role to theconsumer's decision to consume Sariwangi tea, the variable that had the greatest roleto the secondary factor was the social variable with the communality value of17.29%, while the individual variable with the communality value of 10.49% had thelowest role to the consumer's decision to consume Sariwangi tea bags. Consideringthat the seven variables truly have a role to consumer decisions consuming Sariwangitea, then the producer should still pay attention to matters relating to these variables,especially social factors that have the most decisive role.